Windows Internet security : protecting your critical data - Fogie, Seth.; Peikari, Cyrus (Upper Saddle River, NJ : Prentice Hall, 2002)
Windows Internet Security starts by reviewing the threats to your Windows PC: what hackers know about your computer and the Internet, and how they can use that knowledge to attack you. Then, step by step, you'll plan and implement today's most powerful defenses. Windows Internet Security makes security comprehensible, practical-even easy! At home or at work, it's the one indispensable security book for every Windows user and administrator.
Includes bibliographical references (p. 355-357) and index.
cen 16/05/2018
Loans
Keywords: Computer networks; Internet; Computer security